Mid-term clinical outcomes of out-of-hospital cardiac arrest patients treated with targeted temperature management at 34-36 °C versus 32-34 °C - Kleissner, Martin; Sramko, Marek; Kautzner, Josef; Kettner, Jiri (Heart & lung, 2019)
BACKGROUND: Targeted temperature management (TTM) in comatose survivors of out-of-hospital cardiac arrest has been associated with improved neurological outcomes. However, the optimal temperature target for TTM remains unclear. OBJECTIVES: To compare a TTM protocol targeted at 34-36 °C with a protocol targeted at 32-34 °C with reference to both clinical outcomes and acute complications. METHODS: We analyzed a prospective registry of consecutive out-of-hospital cardiac arrest survivors who underwent TTM. We compared patients on a TTM protocol targeted at 34-36 °C (n = 59) with a historical cohort of patients treated at 32-34 °C (n = 116) according to the following parameters: six-month survival, cerebral performance category (CPC) scores, and acute complications. RESULTS: Survival and favorable neurological outcomes (CPC ≤ 2) at six months were 56% and 49%, respectively, in the higher target temperature group vs. 66% and 61%, respectively, in the lower target temperature group (p = 0.18 and 0.13). Acute clinical complications occurred in 1.5% vs. 12% of patients treated at the higher vs. the lower temperature range (p = 0.02). CONCLUSIONS: Patients treated with TTM at 34-36 °C had similar mid-term survival and neurological outcomes as patients treated with TTM at 32-34 °C. However, patients treated within the higher temperature range had fewer acute complications.
Keywords: terapeutická hypotermie; Time Factors; Body Temperature; výsledek terapie; Cardiopulmonary Resuscitation; Middle Aged; registrace; mužské pohlaví; Temperature management; Prospective Studies; Hypothermia, Induced; Resuscitation; Registries; tělesná teplota; Follow-Up Studies; následné studie; kardiopulmonální resuscitace; ženské pohlaví; Humans; prospektivní studie; Cardiac arrest; Out-of-Hospital Cardiac Arrest; časové faktory; lidé středního věku; Hypothermia; zástava srdce mimo nemocnici; Female; Treatment Outcome; lidé; Male